2012
DOI: 10.1039/c2an35162e
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low level optical detection of mercuric ions using biogenic gold nanotriangles

Abstract: Mercury is a serious environmental pollutant known to have detrimental health effects in all life forms. Here, we report the use of biologically synthesized aqueous gold nanotriangles for sensitive and selective optical detection of femto-molar levels of mercury ions by exploiting the high amalgamation tendency of mercury metal towards gold. Aqueous chloroaurate ions were reduced using lemongrass (Cymbopogon flexuosus) leaf extract at room temperature to form gold nanotriangles. Mercuric (Hg(2+)) ions were red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…It may thus be understood that the microwave irradiation of the aqueous extract contained useful organic moieties responsible for the chemical reduction of ionic Ag + to Ag. In this context, the concept of electron transfer mechanisms for reduction of metal ions to form FAgNPs has been reported by several authors [30,37,38]. As the microwave irradiation inactivates enzymes and proteins, the reducing behavior of the extract is most likely due to the presence of flavonoids which are known to have the potential to act as reducing agents [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may thus be understood that the microwave irradiation of the aqueous extract contained useful organic moieties responsible for the chemical reduction of ionic Ag + to Ag. In this context, the concept of electron transfer mechanisms for reduction of metal ions to form FAgNPs has been reported by several authors [30,37,38]. As the microwave irradiation inactivates enzymes and proteins, the reducing behavior of the extract is most likely due to the presence of flavonoids which are known to have the potential to act as reducing agents [32].…”
Section: Resultsmentioning
confidence: 99%
“…Extracts of other plants have also been studied by us [13,15,20,36] and other researchers [34,35,36,37,38]. Recently, MNPs have gained special attention for their promising potential as anticancer agent [12,13,31,36,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the refractive index sensitivity of gold nanorods is linearly proportional to the aspect ratio, facilitating its tunability [97]. Nanostructures of other shapes, including nanocubes [106][107][108][109], nanoshells [110][111][112], nanodiscs [113][114][115], nanotriangles [116,117], nanostars [118][119][120], nanobipyramids [121,122], nanorice [123,124], nanoholes [125,126], and nanocrescents [56,[127][128][129][130], have also been investigated and expanded to nanocubes and nanocuboids enclosed with concave surfaces (Fig. 1).…”
Section: Effect Of Nanoparticle Composition Size and Shape On Plasmomentioning
confidence: 98%
“…Furthermore, as an application of biosynthesized metal nanoparticles, the ability of gold nanotriangles biosynthesized by lemongrass extract was elucidated toward the detection of aqueous mercuric ions at ultra-low femtomolar concentrations [67]. This is an important application of biosynthesized nanomaterials, as mercury is one of the most serious environmental pollutants that are known to have serious detrimental effects on living organisms.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…This is an important application of biosynthesized nanomaterials, as mercury is one of the most serious environmental pollutants that are known to have serious detrimental effects on living organisms. Further experiments revealed that these nanotriangles showed high specificity toward the detection of mercuric ions [67]. In addition, mercury is known to amalgamate with gold thereby enabling the potential use of gold nanoparticles for environmental sensing applications [38,68].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%